2002
DOI: 10.1074/jbc.m201107200
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L and Cathepsin B Mediate Reovirus Disassembly in Murine Fibroblast Cells

Abstract: After attachment to receptors, reovirus virions are internalized by endocytosis and exposed to aciddependent proteases that catalyze viral disassembly. Previous studies using the cysteine protease inhibitor E64 and a mutant cell line that does not support reovirus disassembly suggest a requirement for specific endocytic proteases in reovirus entry. This study identifies the endocytic proteases that mediate reovirus disassembly in murine fibroblast cells. Infection of both L929 cells treated with the cathepsin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
319
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(327 citation statements)
references
References 57 publications
6
319
1
1
Order By: Relevance
“…Endosomal cathepsins, metalloproteases, and secretases mediate cleavage or limited proteolysis of a variety of cellular proteins, leading either to degradation or activation of the respective proteins (31)(32)(33)(34)(35)(36)(37)(38). Furthermore, proteases of the endosomal compartment are known to be involved in the proteolytic processing of a few viral proteins such as the outer capsid proteins of reoviruses (39). However, the NiV F protein is the first viral surface glycoprotein for which it is now shown that site-specific cleavage within endosomes takes place and is required for biological activation.…”
Section: Discussionmentioning
confidence: 99%
“…Endosomal cathepsins, metalloproteases, and secretases mediate cleavage or limited proteolysis of a variety of cellular proteins, leading either to degradation or activation of the respective proteins (31)(32)(33)(34)(35)(36)(37)(38). Furthermore, proteases of the endosomal compartment are known to be involved in the proteolytic processing of a few viral proteins such as the outer capsid proteins of reoviruses (39). However, the NiV F protein is the first viral surface glycoprotein for which it is now shown that site-specific cleavage within endosomes takes place and is required for biological activation.…”
Section: Discussionmentioning
confidence: 99%
“…Reoviruses and Ebola virus use the lysosomal cathepsin proteases to initiate their uncoating processes (24,25). For most substrates, cathepsins act as relatively nonspecific, processive proteases (26), and for these viruses the cathepsins mediate a stepwise proteolysis of the viral structural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin S, a lysosomal cysteine protease, is involved in the processing of MHC class II-associated invariant chain in interferon-c-stimulated microglia (Gresser et al, 2001). Recently, cathepsins were shown to be involved in virus disassembly as well (Ebert et al, 2002). GARG49 is a member of the recently identified glucocorticoid-attenuated response gene (GARG) family, which also includes GARG16 and GARG39 (Smith & Herschman, 1996).…”
Section: Discussionmentioning
confidence: 99%